BK virus‐induced nephritis and cystitis after matched unrelated donor stem cell transplantation: A case report. Issue 12 (7th September 2020) - Gelbrich, Nadine; Stope, Matthias B.; Bekeschus, Sander; Weigel, Martin; Burchardt, Martin; Zimmermann, Uwe
Abstract: Currently, there is no standard therapy for a BK virus infection of the urogenital tract in immunocompromised, stem cell transplanted patients, so that early diagnosis and introduction of supportive measures have the highest response rates to date. Abstract : Currently, there is no standard therapy for a BK virus infection of the urogenital tract in immunocompromised, stem cell transplanted patients, so that early diagnosis and introduction of supportive measures have the highest response rates to date.